ANALISIS USAHA DAN STRATEGI PENGEMBANGAN INDUSTRI RUMAH TANGGA TEMPE KEDELAI DI KABUPATEN KARANGANYAR - Diyah Maharani; Kusnandar Kusnandar; Susi Wuri Ani (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
This study aims to analyze the cost, revenue, profits, profitability, analyze internal and external factors, alternative strategies and prioritize strategies for developing the home industry of soybean tempeh in Karanganyar Regency. The data analysis methods used are 1) business analysis to find out the cost, revenue, profit, profitability; 2) IFE Matrix; 3) EFE Matrix; 4) IE Matrix; 5) SWOT Matrix; 6) QSPM Matrix. The results showed that the average cost of the soybean tempeh home industry business in Karanganyar Regency was IDR14,058,002.96 and the average revenue was IDR15,675,000.00 with an average profit of IDR1,616,997.04 and profitability of 11,50 %. Analysis of the matrix of IFE home industry in soybean tempeh in Karanganyar is strong with a value of 2,877. The results of the EFE matrix also show it is classified as strong with a value of 2,680. The position is in cell 5, namely in the division guarding and maintaining through market penetration strategies and product development strategies. Based on the SWOT matrix, there were eight alternative strategies which were then selected by the four appropriate strategies based on consideration of the IE matrix results, to assess their attractiveness in the QSPM matrix. The highest value of attraction (TAS) of 5,522 is forming institutions or organizations to facilitate access to market, capital, raw material, and technology information.